Cross-reference guide - The Editors, - (Nordic Archaeological Abstracts - NAA, 2003)
The abstracts in NAA are placed in the archaeological period given most prominence in the paper, see Abstracts section finder. Other periods, treated more briefly in the papers, may be found in the cross-reference guide below. As readers are advised to consult the entire general section 1 and the multi-periods/ undated section 11, abstracts from these sections are only exceptionally included. However, under the guide word Iran Age you will find reference to those papers from sections 1 and 11 which deal with the main period lmn Age. General surveys and catalogues are listed in the subject index under Surveys and Catalogues. Readers interested in one or more special subjects are advised to consult the Subject index and the Site index.